2019
DOI: 10.1016/j.heliyon.2019.e01653
|View full text |Cite
|
Sign up to set email alerts
|

Stress-reducing effect of cookies containing matcha green tea: essential ratio among theanine, arginine, caffeine and epigallocatechin gallate

Abstract: The stress-reducing effect of matcha, a high-quality fine-powdered green tea, has recently been clarified by animal experiments and clinical trials. However, the effect of matcha added to confectioneries is not clear. One aim of this study was to evaluate the relationship between matcha components and their stress-reducing effect in mice that were loaded with territorially-based stress. Adrenal hypertrophy, a marker of stress, was significantly suppressed in stress-loaded mice that had ingested matcha componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…Due to the shade-growing of plants intended for matcha production, theanine does not break down. As a result, Tencha leaves contain larger amounts of it compared to other teas [ 49 ]. The relatively high theanine content in matcha tea is responsible for its unique non- bitter taste, and in combination with caffeine provides the taste sensation and umami characteristic of this type of tea [ 48 , 50 ].…”
Section: Chemical Composition Of Japanese Matcha Green Teamentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the shade-growing of plants intended for matcha production, theanine does not break down. As a result, Tencha leaves contain larger amounts of it compared to other teas [ 49 ]. The relatively high theanine content in matcha tea is responsible for its unique non- bitter taste, and in combination with caffeine provides the taste sensation and umami characteristic of this type of tea [ 48 , 50 ].…”
Section: Chemical Composition Of Japanese Matcha Green Teamentioning
confidence: 99%
“…The relatively high theanine content in matcha tea is responsible for its unique non- bitter taste, and in combination with caffeine provides the taste sensation and umami characteristic of this type of tea [ 48 , 50 ]. The combination of l-theanine and caffeine may enhance concentration, vigilance and efficiency to a higher extent than the use of either compound alone [ 51 ], additionally alleviating stress [ 49 ].…”
Section: Chemical Composition Of Japanese Matcha Green Teamentioning
confidence: 99%
“…Theanine (γ-ethylamide-L-glutamic acid) is an extremely rare amino acid in nature, and it has psychoactive properties because it is readily absorbed and permeates the blood-brain barrier to function in the brain [24]. This function leads to reduced mental and physical stress and improved cognition [25][26][27][28][29]. These results suggest that this fermented tea has the effect of improving brain function.…”
Section: Stability Of Main Componentsmentioning
confidence: 99%
“…Studies on a mice model that promoted aging reported improvements in cognitive function [ 14 ] and the promotion of neurogenesis in the developing hippocampus [ 15 ]. In humans, theanine results in improved attention and reaction rates in response to cognitive tasks [ 8 , 16 ], as well as decreased α-amylase activity [ 17 ]. Theanine ingestion affects dopamine, serotonin [ 18 ], tryptophan, and gamma-aminobutyric acid [ 19 ] levels in the brain.…”
Section: Introductionmentioning
confidence: 99%